Pronounced Effects of the Combination of a New Thromboxane Antagonist (GR32191) and Heparin on Bleeding Time in Man - de Boer, A; Kroon, J M; Kroon, C; van Vliet, A; Schoemaker, H C; Breimer, D D; Donoghue, S; Cohen, A F (Thrombosis and Haemostasis, 1992)
Potential pharmacokinetic and pharmacodynamic interactions between two oral doses of GR32191 (40 and 80 mg), a new thromboxane antagonist, and heparin (5,000 IU bolus + 1,000 IU/h for 3 h) were studied in eighteen healthy male volunteers using two separate double-blind, randomised, placebo-controlled, cross-over studies.Mean (range) bleeding time values were 8.4 min (7.5–9.7) during heparin/placebo, 12.1 min (9.2–18.6) (GR32191/placebo) and 16.3 min (11.5–21.4) (GR32191/heparin) in the 40 mg study, while these values were 8.7 min (5.5–15.5), 16.0 min (9.3 – >36.0) and 23.8 min (10.7 – >36.0), respectively in the 80 mg study. Compared to screening values, the combination of 80 mg of GR 32191 and heparin had a greater effect on the bleeding time than the sum of the prolongations after the separate treatments (p = 0.05). In the 40 mg study this was not the case. Pharmacokinetics of heparin (as assessed by plasma anti-Xa and antithrombin activity) and GR32191 were unaltered during coadministration of the two drugs. GR32191 did not influence the effects of heparin on APTT. Heparin slightly diminished the inhibition of collagen induced platelet aggregation by 80 mg of GR32191 and the U-46619 (thromboxane A2-mimetic) induced platelet aggregation remained unchanged. Overall fibrinolytic activity (as evaluated by the fibrin plate test) was similar during all three treatments in the study with 80 mg.The combination of 80 mg of GR32191 and heparin caused a prolongation of the bleeding time which was more than expected on the basis of their individual effects.